Key parameters governing the performance of soft tunnel coating for seismic isolation. - Kim, Dae-Sang (Earthquake engineering & structural dynamics.)
A method to cover a tunnel lining with a soft and thin coating is discussed herein as a possible measure for mitigating seismic damage to tunnels. Long term earthquake observations at different tunnel sites within a variety of alluvial soil deposits have demonstrated that a circular tunnel is liable to deform in such a way that its two diagonal diameters crossing each other expand and contract alternately. Narrowing down vibration modes, in order to discuss this particular and the most important mode, any of the essential items of the soil tunnel system, namely the soil, the coating and the tunnel lining, has only one degree of freedom, allowing the coating effect to be simply evaluated in terms of a limited number of key parameters.